Mechanical properties of polymer nanocomposites with randomly dispersed and cross-linked two-dimensional diamond. (10th November 2022) - Li, Chengkai; Nie, Yihan; Zhan, Haifei; Bai, Jinshuai; Liu, Tianshu; Gu, Yuantong
Abstract: Polymer nanocomposites with excellent mechanical performances have been increasingly sought after in engineering applications such as biotechnology, aerospace, and automotive areas. Through molecular dynamics (MD) simulation, this work systematically assessed the tensile performance of poly(methyl methacrylate) (PMMA) nanocomposite reinforced by randomly dispersed two-dimensional diamond-diamane. It is found that randomly dispersed diamane effectively enhances the tensile properties of PMMA with surface functionalization, and the enhancement effect can be remarkably augmented by cross-linking. Simulations reveal that the enhancement effect can be effectively tailored by the alignment of the diamane fillers. The PMMA nanocomposites exhibit much better tensile performance when the diamane fillers are uniformly aligned along the in-plane direction of the filler. Additional investigations show that larger diamane filler is preferred without cross-linking, while smaller diamane filler should be considered when cross-linking is present. Overall, the impacts of different factors on the tensile properties of PMMA nanocomposites are analysed in-depth in this work, which provides atomistic insights for the preparation of polymer nanocomposites with desired mechanical properties. Graphical abstract: Effective enhancement on the tensile properties of polymer nanocomposites can be achieved by 2D diamond nanofiller. Image 1